2015
DOI: 10.15406/ijcam.2015.01.00006
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine in patients with inflammatory bowel disease: results of a crosssectional study in Slovakia

Abstract: Background and aim: Use of complementary and alternative medicine (CAM) among patients with inflammatory bowel disease (IBD) in Western Europe is common. Data on the frequency of CAM use among IBD patients in Eastern Europe is lacking. The aim of this study was to examine the proportion of CAM use among IBD-patients from Slovakia and to investigate patients' satisfaction with CAM treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…CAM use among IBD patients is becoming increasingly prevalent. In our study focused on IBD patients from a tertiary referral center in Belgium, we report an overall CAM usage of 41.8%, in line with the observations from various other studies [31,[46][47][48]. Although restricted to one center, this is also one among the very first studies to have profiled CAM usage among Belgian IBD patients.…”
Section: Discussionsupporting
confidence: 89%
“…CAM use among IBD patients is becoming increasingly prevalent. In our study focused on IBD patients from a tertiary referral center in Belgium, we report an overall CAM usage of 41.8%, in line with the observations from various other studies [31,[46][47][48]. Although restricted to one center, this is also one among the very first studies to have profiled CAM usage among Belgian IBD patients.…”
Section: Discussionsupporting
confidence: 89%
“…In spite of advances in modern medical science, traditional herbal medicine has continued to be widely used for health maintenance, disease prevention, and even disease treatment in China, Japan, and Korea for thousands of years. Previous studies have shown that 1 out of 2 IBD patients turns to complementary and alternative medicine [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%